INFLUENCE OF PRODUCT QUALITY ON CUSTOMER LOYALTY OF TOYOTA PARTS IN PT. HADJI KALLA SOPPENG BRANCH - Amir, Muhammad (Jurnal Ekonomi Balance, 2019)
Muhammad Amir, 2018. Effect of Product Quality on Customer Loyalty Toyota Parts at PT. Hadji Kalla Branch Soppeng, guided by Kapriani and Yamin Sucipto. This study aims to determine the effect of product quality on customer loyalty in purchasing genuine Toyota parts at PT. Hadji Kalla Soppeng Branch. This study used 53 samples. The analytical method used in this study is deskritif analysis and statistical analysis through simple regression, determination, correlation, and t test. The results of research at PT. Hadji Kalla Toyota Soppeng Branch. Based on the results of the equation Y = 2.63 + 0.96X, correlation analysis (r) = 0.76, correlation coefficient (r2) = 0.58 and hopetesis testing t-count = 8.350> t-table = 1.67528. That there is a significant influence between product quality on customer loyalty at PT. Toyota Hadji Kalla Soppeng Branch.